Application of facial-submental artery island flap in reconstruction of oral and maxillofacial defects - CHEN Weiliang (Editorial Department of Journal of Prevention and Treatment for Stomatological Diseases, 2022)
The facial submental artery island flap (FSAIF) is a fasciocutaneous flap supplied by the facial submental artery. It is in close proximity with many oral and maxillofacial regions, and its tex ture and color are similar to those of the head and face. The flap has a constant and sufficient blood supply, and it is easy to prepare and has high survival rates and few complications. According to the tissue carried, FSAIF can be divided into fasciocutaneous flaps, myocutaneous flaps and simple flaps. The flap can also be made into an osteofasciocutaneous (myocutaneous) flap with a mandible to repair maxillary defects. Because this flap is a pedicled flap, it can greatly shorten the operation time, bed rest time and hospitalization time and has been widely used in repairing medium-sized defects of the oral and maxillofacial region. The indications for FSAIF in repairing maxillofacial defects should be strictly controlled. It can be safely used for benign or malignant tumors without cervical lymph node metastasis. For malignant tumors with cervical lymph node metastasis but without extranodal extension, the flap can be used on the premise of thorough neck dissection. The contraindication is cervical lymph node metastasis and extranodal extension of malignant tumors; therefore, other flaps should be selected for repair.